Flexible fitting to cryo‐EM density map using ensemble molecular dynamics simulations. Issue 16 (1st April 2017) - Miyashita, Osamu; Kobayashi, Chigusa; Mori, Takaharu; Sugita, Yuji; Tama, Florence
Abstract : Flexible fitting is a computational algorithm to derive a new conformational model that conforms to low‐resolution experimental data by transforming a known structure. A common application is against data from cryo‐electron microscopy to obtain conformational models in new functional states. The conventional flexible fitting algorithms cannot derive correct structures in some cases due to the complexity of conformational transitions. In this study, we show the importance of conformational ensemble in the refinement process by performing multiple fittings trials using a variety of different force constants. Application to simulated maps of Ca 2+ ATPase and diphtheria toxin as well as experimental data of release factor 2 revealed that for these systems, multiple conformations with similar agreement with the density map exist and a large number of fitting trials are necessary to generate good models. Clustering analysis can be an effective approach to avoid over‐fitting models. In addition, we show that an automatic adjustment of the biasing force constants during the fitting process, implemented as replica‐exchange scheme, can improve the success rate. © 2017 Wiley Periodicals, Inc. Abstract : For flexible fitting process that involves large and complex conformational transitions, it is important to obtain sufficient conformational sampling in the refinement process by performing multiple fittings trials using different force constants. Automatic adjustment of the biasing force constants during the fitting process, implemented as replica exchange umbrella sampling scheme, can also improve the success rate.